PKM Perumahan Green Village, Kelurahan Ngijo, Gunungpati dalam Pertanian Perkotaan - Dewi, Nur Kusuma; Tri Martuti, Nana Kariada; Hadiyanti, Lutfia Nur; Solichin, Solichin (Life Science, 2020)
Urban agriculture is a part of agriculture that produces, processes and markets agricultural products, especially meeting the daily demands of urban consumers. The purpose of this community service activity is to provide training and urban agricultural assistance for the Green Village community, to support the urban agricultural program being developed by the Semarang City Government and UNNES conservation. Community service activities were carried out at the Green Village Housing, Ngijo Village, Gunungpati District, Semarang, in May-August 2019. The problem solving of community service activities was carried out using a group-based and comprehensive approach method. Meanwhile, to overcome the priority issues faced is carried out by: Training and assistance to grow vegetables that are good and environmentally friendly, provision of seeds and plants that support urban agriculture, and provision of urban agricultural infrastructure. In accordance with the objectives to be achieved, the service activities are as expected. The success in achieving the objectives is shown as follows: coordination is carried out to equalize perceptions of the activities to be carried out. To further increase the capacity of the community in carrying out urban agriculture in their area, training and practice are provided on: planting various types of vegetables. In addition, partners are given various types of vegetable seeds that are easy to breed and cultivate. The conclusions of the activity are: increasing the knowledge and skills of community service partners on how to grow vegetables that are good and environmentally friendly, the availability of seeds and vegetable plants that support the implementation of urban agricultural activities in the community service partner's area, community service partners have carried out urban agricultural sarpras innovations in their areas properly and correctly Pertanian Perkotaan merupakan bagian dari pertanian yang memproduksi, memproses, dan memasarkan produk pertanian, terutama memenuhi permintaan harian konsumen di dalam perkotaan. Tujuan dari kegiatan pengabdian ialah melakukan pelatihan dan pendampingan pertanian perkotaan bagi masyarakat Green Village, untuk mendukung program pertanian perkotaan yang sedang dikembangkan oleh Pemkot Semarang dan konservasi UNNES. Kegiatan pengabdian dilakukan di Perumahan Green Village, Kelurahan Ngijo, Kecamatan Gunungpati, Semarang, pada Bulan Mei- Agustus 2019. Adapun pemecahan masalah dari kegiatan pengabdian dilakukan dengan metode pendekatan berbasis kelompok dan komprehensif. Sedangkan untuk mengatasi persoalan prioritas yang dihadapi dilakukan dengan: Pelatihan dan Pendampingan menanam sayuran yang baik dan ramah lingkungan, penyediaan bibit dan tanaman yang mendukung pertanian perkotaan, serta penyediaan sarpras pertanian perkotaan. Sesuai dengan tujuan yang hendak dicapai, maka kegiatan pengabdian telah sesuai dengan yang diharapkan. Keberhasilan pencapaian tujuan ditunjukkan sebagai berikut: koordinasi dilakukan untuk menyamakan persepsi tentang kegiatan yang akan dilakukan. Untuk lebih meningkatkan kapasitas masyarakat dalam melakukan pertanian perkotaan di wilayahnya, diberikan pelatihan dan praktek tentang: penanaman berbagai jenis sayuran. Disamping itu kepada mitra diberikan berbagai jenis bibit sayuran yang mudah dikembang biakan dan dibudidayakan. Simpulan kegiatan ialah: meningkatnya pengetahuan dan keterampilan mitra pengabdian tentang cara menanam sayuran yang baik dan ramah lingkungan, tersedianya bibit dan tanaman sayuran yang mendukung terselenggaranya kegiatan pertanian perkotaan di wilayah mitra pengabdian, mitra pengabdian telah melakukan inovasi sarpras pertanian perkotaan di wilayahnya dengan baik dan benar